Sustainability, education and character: An Ethics of Virtues for sustainable development - Rodríguez Toro, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
One of the current challenges of Humanity is to safeguard its existence as a species, through sustainable development. It is a goal with strong political, economic, social, scientific and technological implications, because it implies the adoption of a different civilizational model, in which the advancement of our knowledge and lifestyles do not continue altering the balance of Nature. The purpose of this article is to analyze the ethical-pedagogical dimension of such a challenge, referring to the need to form the moral character of children and adolescents according to an Ethics of Virtue.